Natural White Pinkish Fairness Advertisement - Ignacia Petrina (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study observes the perceived meanings towards perceived meanings stated by people with different skin colors towards a skin whitening product advertisement. The subjects for this research are people with dark and fair skin. The writer used the theory of perceived meaning, semiosis, representation, interpretation, and light-skinned beauty in Indonesia to analyze the perceived meanings. The study used descriptive qualitative approach to reveal the perceived meanings of the respondents in a systematic way. From this study, it was found that skin color was one of the factors that affects the process of perceived meaning. Dark skin respondents produced perceived meanings that dark skin was beautiful. Meanwhile, fair skin respondents agreed that fair skin equaled beauty. However, they also produced similar perceived meanings due to the similar culture and common stereotype. Key words: Advertisement, Verbal Expressions, Visual Expressions, Perceived Meaning.